2012
DOI: 10.1177/0961203312447668
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum β2-microglobulin is associated with clinical and immunological markers of disease activity in systemic lupus erythematosus patients

Abstract: The objective of this study was to explore the relationship between serum levels of β2-microglobulin (β2MG), which some studies suggest reflect disease activity in systemic lupus erythematosus (SLE), and various clinical and immunological markers of disease activity in SLE. Twenty-six SLE patients and 10 healthy controls were included. Disease activity was assessed by: SLEDAI, 24 hr-proteinuria, circulating levels of complement C3, anti-double-stranded DNA (anti-dsDNA), β2MG and various pro-inflammatory and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 32 publications
3
41
0
Order By: Relevance
“…Several soluble cytokine receptors and adhesion molecules [IL-2RA, TNF receptor 1 (TNFR1), TNFR2, and vascular cell adhesion molecule 1 (VCAM-1)] demonstrated elevated levels in DM or PM patients, which was consistent with previous reports [17–19]. Our results also indicated overexpression of ANGPT2 and soluble B2M, which has been reported in SLE and SSc, but not IIMs [20–22]. Elevated serum ANGPT2 levels were only seen in the subset of IFN-hi patients (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Several soluble cytokine receptors and adhesion molecules [IL-2RA, TNF receptor 1 (TNFR1), TNFR2, and vascular cell adhesion molecule 1 (VCAM-1)] demonstrated elevated levels in DM or PM patients, which was consistent with previous reports [17–19]. Our results also indicated overexpression of ANGPT2 and soluble B2M, which has been reported in SLE and SSc, but not IIMs [20–22]. Elevated serum ANGPT2 levels were only seen in the subset of IFN-hi patients (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Another study on 26 lupus patients, by Hermansen et al, 11 found that serum β2M showed correlations with cytokines such as interleukin (IL)-6, IL-8, IL-10 and IL-18, and with serum interferon-α. These authors believed that the increased β2M levels in active SLE reflected the overall immunological activity.…”
Section: Discussionmentioning
confidence: 99%
“…Higher serum levels are seen in patients with systemic lupus erythematosus and adult-onset Still disease, especially in those with active diseases and hemophagocytic syndrome (268, 301). After therapy, the serum β 2 M level decreased significantly (268).…”
Section: β2m In Non-renal Diseasesmentioning
confidence: 99%